2022
DOI: 10.3390/separations9070158
|View full text |Cite
|
Sign up to set email alerts
|

Validation of an Analytical Method for the Determination of Manganese and Lead in Human Hair and Nails Using Graphite Furnace Atomic Absorption Spectrometry

Abstract: This article describes the validation of analytical methods for the determination of Manganese (Mn) and lead (Pb) by graphite furnace atomic absorption spectrometry (GFAAS) in human hair and nail samples. Method validation parameters such as linearity, repeatability, reproducibility, and precision were determined. In addition, the limit of detection (LOD), the limit of quantification (LOQ), and measurement uncertainty were calculated. The developed method was linear in the concentration ranges of 0.001–0.015 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
0
1
0
Order By: Relevance
“…Choosing suitable analysis methods and instruments for PTEs is a severe challenge due to the complexity of the human milk matrix (Draghici et al, 2011;Zeiner et al, 2007). Accordingly, many analytical techniques have been used for measuring PTEs, such as Thin layer chromatography(TLC) (Jumde and Gurnule, 2015;Kholghi et al, 2020), UV-VIS spectrometry (Hasankola et al, 2020;Zhou et al, 2019), Atomic absorption spectrometry (AAS) by Flame Atomic Absorption(FAA) (Muhib et al, 2016;Wang et al, 2015), Graphite Furnace Absorption (GFA) (Forero-Mendieta et al, 2022;Zhong et al, 2016) and Vapor Generation Absorption(VGA) (Mostafavi and Ebrahimi, 2019;Perelonia et al, 2021), X-ray fluorescence (XRF) (Byers et al, 2019;Zhou et al, 2018), Electrochemical Methods (Cui et al, 2015;Ding et al, 2021), Inductively Coupled Plasma Optical Emission Spectroscopy (ICP-OES) (Fathabad et al, 2018;Yamini and Safari, 2018) and Inductively coupled plasma mass spectrometry (ICP-MS) (Ashrit et al, 2018;Zhang et al, 2020). In some studies, combining at least two analytical methods helps achieve the best results in different matri (Kwon et al, 2018;Li et al, 2021).…”
Section: Analytical Methods and Instruments For Measuring Ptes In Hum...mentioning
confidence: 99%
“…Choosing suitable analysis methods and instruments for PTEs is a severe challenge due to the complexity of the human milk matrix (Draghici et al, 2011;Zeiner et al, 2007). Accordingly, many analytical techniques have been used for measuring PTEs, such as Thin layer chromatography(TLC) (Jumde and Gurnule, 2015;Kholghi et al, 2020), UV-VIS spectrometry (Hasankola et al, 2020;Zhou et al, 2019), Atomic absorption spectrometry (AAS) by Flame Atomic Absorption(FAA) (Muhib et al, 2016;Wang et al, 2015), Graphite Furnace Absorption (GFA) (Forero-Mendieta et al, 2022;Zhong et al, 2016) and Vapor Generation Absorption(VGA) (Mostafavi and Ebrahimi, 2019;Perelonia et al, 2021), X-ray fluorescence (XRF) (Byers et al, 2019;Zhou et al, 2018), Electrochemical Methods (Cui et al, 2015;Ding et al, 2021), Inductively Coupled Plasma Optical Emission Spectroscopy (ICP-OES) (Fathabad et al, 2018;Yamini and Safari, 2018) and Inductively coupled plasma mass spectrometry (ICP-MS) (Ashrit et al, 2018;Zhang et al, 2020). In some studies, combining at least two analytical methods helps achieve the best results in different matri (Kwon et al, 2018;Li et al, 2021).…”
Section: Analytical Methods and Instruments For Measuring Ptes In Hum...mentioning
confidence: 99%
“…The recovery rate was found to be 93 to 100%. Some researchers have developed the graphite furnace atomic absorption spectrometry (GFAAS) analytical method for determining manganese (Mn) and Pb in a target sample [55]. It was reported that the developed method showed linearity in the range from 0.001 to 0.015 and from 0.002 to 0.020 µg/L for Mn and Pb, with a recovery rate from 84.80% to 107.98%, respectively.…”
Section: Atomic Absorption Spectrophotometry (Aas)mentioning
confidence: 99%
“…Many metals in biological materials occur in trace amounts, requiring sensitive instrumental techniques. The most commonly used are atomic absorption spectroscopy (AAS) with atomization in a graphite furnace (in a few cases in a flame) [ 11 , 12 , 13 , 14 ], optical emission spectrometry [ 15 , 16 ], mass spectrometry [ 4 , 5 , 6 , 17 , 18 ] with plasma as a source of excitation or ionization of elements (ICP OES, ICP MS), and total reflection X-ray fluorescence spectrometry (TXRF) [ 19 , 20 ]. In addition to the high operating costs typical of these techniques, they require sample mineralization [ 5 , 6 , 16 , 21 ] or extraction combined with preconcentration [ 13 , 16 , 18 , 22 ].…”
Section: Introductionmentioning
confidence: 99%